PENGARUH TERAPI TERTAWA TERHADAP HOT FLASHES PADA WANITA MENOPAUSE - Juliani Juliani; Sri Utami; Oswati Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hot flashes are the hot complaint on the face, arms, neck, upper body, and chest area, as well as sweats that are common in menopausal women. This study aimed to determine the effect of laughing therapy on hot flashes in menopausal women. This research used "Quasi Experimental Design" with "Non-Equivalent Control Group design". This research was conducted at Labuh Baru Timur Subdistrict, Payung Sekaki Sub District, Pekanbaru on 34 people with 17 people as experiment group and 17 people as control group with a non probability sampling technique that purposive sampling. Measuring instrument used questionnaire hot flashes score. Laughing therapy was given experimental group 2 times for 10-15 minutes. The analysis used univariate analysis to determine the frequency distribution and bivariate used alternative test of Wilcoxon and Mann-Whitney. The results showed significant differences in hot flashes score after the laughing therapy between the experimental group and the control group with p value = 0.001 < α (0.05). It could be concluded that laughing therapy was effective on decreaseed hot flashes score in menopausal women. The results of this study are expected to be one of the nursing interventions to reduce the score of hot flashes in menopausal women.Keywords: Hot Flashes, Laughing Therapy, Menopausal